Redefining the model: cooperatives in the just ecosocial transition paradigm - Olaizola-Alberdi, Jon; Imaz Alias, Oier; Bollain, Julen; Herce-Leceta, Beñat (Iberoamerican Journal of Development Studies, 2025)
This study examines the integration of cooperativism within the just ecosocial transition paradigm, addressing the urgent need for sustainable and equitable economic development. It analyses the alignment of cooperative principles with multidimensional justice considerations, including environmental, social, climate, energy and labour, to identify a framework where cooperatives act as key agents in promoting a just ecosocial transition. A narrative literature review was employed to critically analyse the theoretical and practical interconnections between cooperativism and just ecosocial transition, revealing both opportunities and inherent contradictions. The results and discussion indicate that, although cooperatives inherently support the dimensions of justice crucial to a just ecosocial transition, practical implementation often reveals challenges, particularly in balancing these ideals with market dynamics. A proposal has been made to overcome those challenges based on impact assessment methodologies, such as the Theory of Change.
Keywords: cooperativism; just ecosocial transition; impact assessment; sustainable development; Theory of Change